1995
DOI: 10.1039/an9952001221
|View full text |Cite
|
Sign up to set email alerts
|

Dilute acid digestion procedure for the determination of lead, copper and mercury in traditional Chinese medicines by atomic absorption spectrometry

Abstract: A sample preparation procedure using 10% v/v HN03 was successfully applied to the determination of Pb, Cu and Hg in traditional Chinese medicines. It provides good recoveries of Pb, Cu and Hg, requires small volumes of concentrated acid and is free from reagent and procedural blank problems. A number of Chinese medicines were analysed using the proposed method. The results obtained were comparable to those obtained by other standard procedures. Using a 3 g sample, the detection limit for Pb was about 4 pg g-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Cr content in seedlings (2 g dry weight, DW) was determined by using 10% v/v HNO 3 acid digestion procedure as described in [47] and expressed as µg g −1 DW.…”
Section: Methodsmentioning
confidence: 99%
“…Cr content in seedlings (2 g dry weight, DW) was determined by using 10% v/v HNO 3 acid digestion procedure as described in [47] and expressed as µg g −1 DW.…”
Section: Methodsmentioning
confidence: 99%
“…Plants are normally exposed to toxic heavy metals when they are grown in polluted areas as in roadways or exposed to polluted soil, that are contaminated by agricultural pesticides and irrigation water in conditions where they are collected, dried and processed, transport and storage conditions (Abou-Arab and Abou-Donia, 2000; Pethkar et al, 2001;Khan et al, 2001). Hence, raw medicinal plants are a potential source of toxic metal exposure for man and animals (Cataldo and Wildung, 1978;Al-Saleh and Chudasama, 1994;Chow et al, 1995;Pethkar et al, 2001), therefore raw medicinal herbs that are used for consuming as raw herbs as well as finished products, need to be checked for the presence of heavy metals, pesticides, bacterial or fungal contamination (WHO, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The use of diluted nitric acid solution is not frequent, but it was already demonstrated that it is effective for extraction of metals in biological samples at room temperature (De Boer and Maessen 1983) or by heating (Chow et al 1995;Minami, Honjyo, and Atsuya 1996;Zhou et al 1996). These procedures could be considered extraction procedures because none of them were tailored to promote the oxidation of organic compounds.…”
Section: Introductionmentioning
confidence: 98%